Kaitiakitanga: Ki Runga Ki Raro - Ruka, Tanya Maree (Auckland University of Technology, 2012)
Nga Whenua: Maori ki tona ake ao Landscape: Documenting and developing a Maori World View The kaupapa of this project is to reconsider landscape from a Maori worldview. This project seeks to unveil nga whenua through the development of a Maori metaphorical narrative - North and South - Ki Runga ki Raro. By implementing Maori epistemology, cosmology and mythologies and juxtaposing of Indigenous and Western belief systems regarding land, landscape and Stewardship. Then weaving together these ideas; highlighting similarities and bridging subjective/ objective divides based on the philosophy of Te Kore, the nothing and nothingness. Intrinsically based in the epistemologies of my Tupuna, ancestors; my practice seeks to explore how we might address the poetic and cyclical nature of past, present and future as it adheres to Maori lore - I nga waa o mua.
Keywords: Landscape; Maori; Art; Digital; Video; Installation; Narrative; Poesy; Political; Wairuatanga; Tukutuku; Weaving